Metarhizium macrosemiae sp. nov. and the anamorph of M. guniujiangense on adult cicada from Guniujiang Nature Preserve, southeastern China - Chen, Ming-Jun; Lin, Yan; Wang, Ting; Zhang, Sheng-Li; Huang, Bo (Phytotaxa, 2022)
We conducted morphological evaluations and multi-locus phylogenetic analyses of SSU, LSU, EF-1a, RPB1 and RPB2 genes for Metarhizium strains infecting adult cicada from Guniujiang Nature Preserve, southeastern China. A new species Metarhizium macrosemiae is described. M. macrosemiae is the phylogenetic sister species of M. chaiyaphumense / M. takense. M. macrosemiae is distinguished morphologically from M. chaiyaphumense by its host, growth rate on agar, and size of the phialides. It differs significantly from M. takense in colony colour, growth rate on agar, and the presence of macroconidia on SDYA/4. Additionally, comparison of five gene sequences with those of M. guniujiangense type strain revealed that two strains on adult cicada are asexual morph of M. guniujiangense. We illustrate and describe this previously unreported asexual morph of M. guniujiangense on adult cicada.